Faktor-Faktor Yang Berhubungan Dengan Pemberian ASI Eksklusif - Oktavin Yollah Umboh; Adrian Umboh; David E Kaunang (Universitas Sam Ratulangi, 2021)
Background: Breastfeeding without other food can meet the growing needs of a baby up to six months of age. The achievement of exclusive breastfeeding in Indonesia has not satisfactory. The purpose of this study was to determine the factors correlated with exclusive breastfeeding. Methode: This research is a quantitative study using an analytical survey method and a cross sectional approach from November 2018 to March 2019 in the Teling Atas Community Health Center in Manado, involving 140 mothers as a sample. The research variables were measured using a questionnaire and then analyzed using chi square and multiple regression test. Result: This study showed that there was a significant relationship between maternal occupation (p 0,006) and exclusive breastfeeding, while maternal education, maternal knowledge, family support and motivation of health workers had no significant relationship with exclusive breastfeeding (p>0,05). The results of multivariate analysis showed that maternal knowledge greatly influenced exclusive breastfeeding (p 0.04 and OR 2.531). Conclusion: The conclusion of this study is that the maternal occupational factors had a significant correlation with exclusive breastfeeding. However, the community health center should be more active in motivating pregnant and breastfeeding mother about the benefits and methods of exclusive breastfeeding.